From the expression of prime numbers to Goldbach conjecture (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Operation instead of screening method to solve the congruence equation. Discussion on the expression of prime numbers and its applications; Setting up the residual model to solve the problem of related distribution; The problem of solving the problems about prime pairs of even numbers with the correspondence model of even numbers.